2006
DOI: 10.1002/j.2161-1874.2006.tb00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual and Moral Development of Substance Abuse Counselors: Implications for Training

Abstract: The relationship among substance abuse counselors' education, experience, recovery status, and cognitive development (conceptual complexity and moral reasoning levels) was examined in a simultaneous multiple regression. Significant relationships were found between counselors' level of conceptual complexity and moral reasoning and their education. Implications for counselor training are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 18 publications
0
25
1
Order By: Relevance
“…SACs (N = 227) with an associate degree/high school diploma scored higher than those with a bachelor/graduate degree, suggesting respondents with less education were more sensitive to ethical dilemmas. These findings contradict previous research (e.g., Rest & Narvaez, 1994;Sias, Lambie, & Foster, 2006), and Toriello and Benshoff (2003) suggested the disparity may have resulted from respondents' differing interpretations of the question, "How difficult would it be for you to choose between the two conflicting actions?" (p. 93).…”
Section: Moral Reasoning Of Sacs: Related Researchcontrasting
confidence: 98%
“…SACs (N = 227) with an associate degree/high school diploma scored higher than those with a bachelor/graduate degree, suggesting respondents with less education were more sensitive to ethical dilemmas. These findings contradict previous research (e.g., Rest & Narvaez, 1994;Sias, Lambie, & Foster, 2006), and Toriello and Benshoff (2003) suggested the disparity may have resulted from respondents' differing interpretations of the question, "How difficult would it be for you to choose between the two conflicting actions?" (p. 93).…”
Section: Moral Reasoning Of Sacs: Related Researchcontrasting
confidence: 98%
“…Additionally, because both ethical decision making and social-cognitive maturity are developmental constructs, these findings suggest that the promotion of developmental growth may be more difficult in a short period of time than the acquisition of specific content knowledge. Specifically, based on the tenets of Deliberate Psychological Education Model (Mosher & Sprinthall, 1971) and research (e.g., Sias, Lambie, & Foster, 2006), interventions designed to promote developmental constructs such as social-cognitive development and moral reasoning (ethical decision making) should be a minimum of 6 months to 1 year in length. Within counselor education programs, it is suggested that developmental interventions be facilitated for at least three consecutive semesters (Lambie & Sias, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In the substance abuse counseling field, staff members come from a variety of backgrounds and educational experiences (Sias, Lambie, & Foster, 2006). They may come from the fields of counseling, rehabilitation, psychiatric nursing, or medicine.…”
Section: Unique Issues Related To the Eield Of Substance Abuse Counsementioning
confidence: 99%
“…Many staff members in substance abuse treatment programs are recovering from the same disorder as their clients (Sias et al, 2006). Recovering counselors bring a personal perspective to the treatment environment that can benefit clients.…”
Section: Unique Issues Related To the Eield Of Substance Abuse Counsementioning
confidence: 99%
See 1 more Smart Citation